2009
DOI: 10.1510/icvts.2009.208231
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoenergetic function and troponin T release following cardioplegic arrest induced by St Thomas' and histidine-tryptophan-ketoglutarate cardioplegia – an experimental comparative study in pigs☆☆☆

Abstract: The study compares the single dose histidine-tryptophan-ketoglutarate (HTK) cardioplegia to the repeatedly delivered St Thomas' Hospital Solution (STHS) with respect to preservation of left ventricular mechanoenergetics and leakage of troponin T in a porcine experimental model. Fourteen pigs were randomized to a single infusion of 30 ml/kg HTK cardioplegia (n=7) or 500 ml STHS (n=7) followed by 200 ml after 20 and 40 min. After 1 h of aortic cross-clamping on cardiopulmonary bypass (CPB), the pigs were weaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 8 publications
1
21
1
Order By: Relevance
“…This is the case with the Bretchneider's histidine‐tryptophan‐ketoglutarate (HTK) solution. These two strategies have been compared clinically and experimentally ; however, there is no consensus on which solution provides a better myocardial protection. The clinical studies comparing the two solutions are mostly on adult patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case with the Bretchneider's histidine‐tryptophan‐ketoglutarate (HTK) solution. These two strategies have been compared clinically and experimentally ; however, there is no consensus on which solution provides a better myocardial protection. The clinical studies comparing the two solutions are mostly on adult patients.…”
mentioning
confidence: 99%
“…compared clinically and experimentally (2)(3)(4)(5); however, there is no consensus on which solution provides a better myocardial protection. The clinical studies comparing the two solutions are mostly on adult patients.…”
mentioning
confidence: 99%
“…This might attributed to the good qualities of HTK, including high buffer capacity, ketoglutarate to improve the ATP energy production, and tryptophan to stabilize the cell membrane. 12 On the other hand, immature hearts have higher resting concentrations of free amino acids which are consumed by ischemic myocardium, 13 and they can produce more alanine, succinate, and malate during ischemia, and have better recovery of postischemic aerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Experimental studies have shown, however, that HTK solution provides inadequate cardioprotection when compared to CBC. 6,7 The relative advantage of blood cardioplegia in relation to crystalloid cardioplegia is still the subject of debate in pediatric cardiac surgery. 8,9 Angeli et al 10 reported that HTK solution was applied to newborns undergoing arterial switch operations with a mean of 98 minutes of cardiac arrest; however, the authors did not use any control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation